MENGEKSPLORASI HUBUNGAN ANTARA DANA OTONOMI KHUSUS DAN BELANJA MODAL DI DAERAH ACEH DAN PAPUA BARAT - Fitri, Aisyah Dasfania; Asmara, Jhon Andra (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study aims to determine the effect of regional own revenue and revenue sharing funds on expenditure capital with special autonomy funds as moderators in regencies/cities in Aceh and West Papua in 2019 2021. This type of research is quantitative using secondary data in the form of Examination Reports on each district/city in Aceh and West Papua during the 2019 2021 period. The research method uses the census method or the entire population. The data analysis method used is multiple linear regression analysis and Moderated Regression Analysis (MRA) using the SPSS version 25 application. The results of the study show (1) regional original income and revenue sharing simultaneously affect capital spending in Aceh and West Papua; (2) regional own-source revenues and profit-sharing funds partially affect capital spending in Aceh and West Papua; (3) special autonomy funds can moderate the influence of regional original revenue sharing on spending capital in Aceh and West Papua.